Correcting the Output Conductance for Self-Heating in InAlAs/InGaAs HBTs - Weiß, Oliver; Baureis, Paul; Kellmann, Nikolai; Weber, Norbert; Weigel, Robert (IEEE Transactions on Electron Devices, 2006)
Two methods to correct the output characteristics of a heterojunction bipolar transistor (HBT) for self-heating, which especially suit material systems with low thermal conductivity and high temperature dependence of the current gain, are presented. The first and more conventional approach uses direct measurements of dc parameters (thermal conductivity and the temperature dependence of the current gain). The second method is based on measurements of small-signal parameters. Both procedures are applied to measurements on InAlAs/InGaAs HBTs. These methods result in reconstructed output characteristics that show a temperature-independent behavior and little gradient in the linear region. The methods presented in this paper may be used to investigate the electric field distribution and the avalanche currents of transistors with low thermal conductivity and high temperature dependence of the current gain
elib2cris::1512001600,weiss2006a